PELATIHAN PENGELOLAAN KEUANGAN PETANI DI DESA AMPRENG KECAMATAN LANGOWAN BARAT KABUPATEN MINAHASA (Farmer Financial Management Training In Ampreng Village Langowan Barat Sub District Minahasa Regency) - Charles R. Ngangi; Jean Fanny Junita Timban (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
Financial management is the management of financial functions that must be carried out by all people who have responsibilities in the field / financial aspect. Various breakthroughs have been implemented, but the welfare of farmers from time to time has not shown significant improvement. Therefore, one of the things that needs to be studied is the financial management which is closely related to the financing and income of these farmers. The right solution includes assistance in the form of training to improve knowledge and skills in financial management of the farming business.            This program is an applied program in order to increase partner income in Ampreng Village, Langowan Barat District. The increased income that group members receive from training activities stems from the process of transferring knowledge and technology which can be directly applied in the field. The knowledge and technology that will be transferred to this activity are financial management techniques. In its implementation, this program will refer to a synergistic pattern between experts and practitioners from Sam Ratulangi University Manado and the village government of Ampreng.            This program is designed as an answer to the problems of farmers who are not aware of the importance of planning and financial management. Through the implementation of this designed program, training and assistance will be provided for members of farmer groups. The operationalization of the community partnership program consists of 3 stages, namely the preparation stage, the implementation stage and the program sustainability plan. The expected end result is the increased knowledge of bookkeeping, increased income for group members as well as institutional and management.Keywords: Financial Management, Farmers